Perdida de empatía por parte del personal de enfermería hacia el familiar del paciente crítico - Sánchez Andrade, Christian Renato (2025)
Nursing care in the critical care area takes place in a hostile environment, where serious pathologies are constantly repeated. Factors such as the use of advanced technology, the loneliness experienced by professionals in this area and the lack of gratitude on the part of critical patients' relatives contribute to the decrease of empathy in nursing staff. The objective of the article is to identify the main causes that trigger the loss of empathy in nurses towards the relatives of critically ill patients. The research had a quantitative and cross-sectional approach, through the application of a survey to 14 nursing professionals working in the critical care area. The results showed that the constant exposure to an environment dominated by technology, the repetition of severe cases and the lack of recognition by family members generate a decrease in empathy in nurses. Long working hours affect staff emotionally, leading to burnout and reducing their ability to engage affectively with patients and their families. In conclusion, the loss of empathy in nursing is associated with the combination of several elements that affect each professional differently. The accumulation of similar experiences, long shifts and a cold and hostile work environment can cause nursing staff to become less empathetic and even more distant or aggressive in their dealings with patients and their families.